2015
DOI: 10.1186/s12879-015-0929-5
|View full text |Cite
|
Sign up to set email alerts
|

Medical students’ attitude towards influenza vaccination

Abstract: BackgroundInfluenza vaccination is recommended for all healthcare personnel (HCP) and most institutions offer vaccination for free and on site. However, medical students do not always have such easy access, and the predictors that might guide the motivation of medical students to get vaccinated are largely unknown.MethodsWe conducted a cross-sectional survey study among pre-clinical medical students in a German University hospital to assess the social cognitive predictors of influenza vaccination, as well as r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 24 publications
2
22
0
8
Order By: Relevance
“…As a matter of fact, an education that strengthens and focuses on prevention strategies may represent further driving force that increases the vaccination coverage. [27][28][29] We could not assess whether the vaccination campaign strategies we adopted could reach all MRs and, if they did, to what extent they helped to increase the influenza vaccination coverage.…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of fact, an education that strengthens and focuses on prevention strategies may represent further driving force that increases the vaccination coverage. [27][28][29] We could not assess whether the vaccination campaign strategies we adopted could reach all MRs and, if they did, to what extent they helped to increase the influenza vaccination coverage.…”
Section: Discussionmentioning
confidence: 99%
“…One study reports a lack of knowledge, while the others highlight the reasons for accepting or refusing influenza vaccination. [23][24][25][26]29 Self-protection, patient protection, free offer were the reasons for vaccination acceptance. Forgetfulness, concerns about side-effects, low risk-perception were the reasons for vaccination refusal.…”
Section: Discussionmentioning
confidence: 99%
“…Forgetfulness, concerns about side-effects, low risk-perception were the reasons for vaccination refusal. [23][24][25][26]29 One of the mentioned study demonstrated that occupational risk perception is greater for Hepatitis B than influenza. 23 The determinants of vaccination acceptance highlighted in the cited surveys are similar to ones analyzed in our study, but none of these studies analyzed the potential role of academic institution in the vaccine promotion and this is the principal strength of our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Daher scheint es unerlässlich, die im nationalen und internationalen Forschungsfokus eher selten betrachtete Berufsgruppe der Hebammen näher zu beleuchten [10,11,16,[18][19][20]. Hierbei erweckt insbesondere die Subgruppe der Hebammenschülerinnen Interesse, die im Gegensatz zum ärztlichen Nachwuchs noch nicht national oder international untersucht wurde [21]. Ziel dieser Studie war, erstmalig Einstellungen und Wissensstand bezüglich Impfungen im Allgemeinen sowie der Influenza-Impfung im Speziellen von Hebammenschülerinnen zu erfassen.…”
Section: Introductionunclassified